Spaces of Encounter: Art and Revision in Human-Animal Relations - Snæbjörnsdóttir, Bryndis (2009)
An exhibition is been held in connection to the public defence. This PhD project explores contemporary Western human relationships with animals through a ‘relational’ art practice. It centres on three art projects produced by Snæbjörnsdóttir/Wilson – nanoq: flat out and bluesome; (a)fly; and seal – all utilize lens-based media and installations. Discourses on how humans construct their relationship with animals are central to all three projects. The first one looks at polar bears, the second at pets, and the third at seals, in a variety of different sites within clearly defined contexts and geographical locations. The thesis explores the visual art methodologies employed in the projects, tracing in turn their relationship to writings about human-animal relations. This includes both writings researched in the making of the works and those considered retrospectively in the reflections on each art project. These artworks engage their audiences in a series of ‘encounters’ with the subject through simultaneous meetings of duality, e.g. haunting vs. hunting, perfection vs. imperfection and the real vs. the unreal. These dualities are important in theorizing this relational space in which the eclipse of the ‘real’ animal in representation occurs and in formulating questions embedded in and arising from the artworks on the construction and the limits of these boundaries. The ‘three registers of representation’, as put forward by the artists Joseph Kosuth and Mary Kelly, have further helped to frame and develop the thinking, concerning both the mechanisms within the works and their perceived effects.